Adult Attachment Style as a correlate of Distorted Thinking in Young Adults with Adverse Childhood Experiences - Singh, Suyesha; Jain, Prashasti; Singh, Sheron (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to investigate the relationship between cognitive distortions and attachment styles in young adults. Experiences in early years of life play a pivotal role in the psychological and social development of an individual. The current study aimed at studying the role of cognitive distortions in shaping the attachment styles of an individual. The sample for the study comprised young adults both males and females of 18- 25 years of age. Adverse Childhood Experiences (ACE) Questionnaire by Felitti et al., (1998) was used as a screening tool. Thereafter the screened sample of 220 subjects was administered the Cognitive Distortion Scale by Briere (2000) and Adult Attachment Scale by Collins & Read (1990). A significant relationship was found between cognitive distortions and adult attachment styles.